Investigation of the Obesity Paradox in Chronic Obstructive Pulmonary Disease, According to Smoking Status, in the United States. Issue 11 (5th September 2019) - Wu, Tianshi David; Ejike, Chinedu O; Wise, Robert A; McCormack, Meredith C; Brigham, Emily P
Abstract: An obesity paradox in chronic obstructive pulmonary disease (COPD), whereby overweight/obese individuals have improved survival, has been well-described. These studies have generally included smokers. It is unknown whether the paradox exists in individuals with COPD arising from factors other than smoking. Nonsmoking COPD is understudied yet represents some 25%–45% of the disease worldwide. To determine whether the obesity paradox differs between ever- and never-smokers with COPD, 1, 723 adult participants with this condition were examined from 2 iterations of the National Health and Nutrition Examination Survey (1988–1994, 2007–2010), with mortality outcomes followed through December 2011. Using Cox proportional hazards models, adjusted for sociodemographic factors, lung function, and survey cycle, ever/never-smoking was found to modify the association between body mass index and hazard of death. Compared with normal-weight participants, overweight/obese participants had lower hazard of death among ever-smokers (for overweight, adjusted hazard ratio (aHR) = 0.56, 95% confidence interval (CI): 0.43, 0.74; for obesity, aHR = 0.66, 95% CI: 0.48, 0.92), but never-smokers did not (overweight, aHR = 1.41, 95% CI: 0.66, 3.03; obesity, aHR = 1.29, 95% CI: 0.48, 3.48). An obesity paradox appeared to be absent among never-smokers with COPD. This, to our knowledge, novel finding might be explained by pathophysiological differences between smoking-related and nonsmoking COPD or by smoking-associated methodological biases.